2013
DOI: 10.1371/journal.pone.0065550
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Haplotypes Associated with Prenatal Death in Dairy Cattle and Identification of Deleterious Mutations in GART, SHBG and SLC37A2

Abstract: The regular decrease of female fertility over time is a major concern in modern dairy cattle industry. Only half of this decrease is explained by indirect response to selection on milk production, suggesting the existence of other factors such as embryonic lethal genetic defects. Genomic regions harboring recessive deleterious mutations were detected in three dairy cattle breeds by identifying frequent haplotypes (>1%) showing a deficit in homozygotes among Illumina Bovine 50k Beadchip haplotyping data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
192
4
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(219 citation statements)
references
References 35 publications
13
192
4
10
Order By: Relevance
“…In fact, significant effects on calving rate were observed between matings of carrier sires and daughters of carrier sires, confirming that the haplotypes harbour embryonic lethal mutations (VanRaden et al, 2011;Fritz et al, 2013). Recently, in Holstein, Montbeliarde and Normande cattle Fritz et al (2013) identified 34 candidate haplotypes (P < 10 −4 ) including Brachyspina, CVM, HH1 and HH3 previously reported by VanRaden et al (2011) and three novel mutations that had effects on protein structure. The impact of these mutations is likely to increase as inbreeding accumulates in intensively selected cattle breeds.…”
Section: Genomics Of Reproductive Performance For Animal Breedingsupporting
confidence: 58%
“…In fact, significant effects on calving rate were observed between matings of carrier sires and daughters of carrier sires, confirming that the haplotypes harbour embryonic lethal mutations (VanRaden et al, 2011;Fritz et al, 2013). Recently, in Holstein, Montbeliarde and Normande cattle Fritz et al (2013) identified 34 candidate haplotypes (P < 10 −4 ) including Brachyspina, CVM, HH1 and HH3 previously reported by VanRaden et al (2011) and three novel mutations that had effects on protein structure. The impact of these mutations is likely to increase as inbreeding accumulates in intensively selected cattle breeds.…”
Section: Genomics Of Reproductive Performance For Animal Breedingsupporting
confidence: 58%
“…In dairy cattle, 25 haplotypes which were not observed in the homozygous state were identified at specific chromosomal positions in particular breeds (van Raden et al 2011;Fritz et al 2013;Sahana et al 2014;Cole et al 2015). It is argued that these positions harbour genes with recessive lethal mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these losses remain unclear and likely result from several factors, including embryonic lethal genes (8,9), environmental stressors (7), and endometrial condition (10). Cloning of cattle by somatic cell nuclear transfer (SCNT) induces perturbations in conceptus development and greatly increases the probability of developmental arrest before and after implantation (11,12).…”
mentioning
confidence: 99%